Impacted second molar and third molar mandibular dextra and its management: a case report - Tajrin, Andi; Rusdin, Muhammad HS. (Hasanuddin University, 2020)
Objective: Impacted tooth is an abnormally tooth eruption, usually caused by adjacent tooth near it or pathologic tissue. Clinically, if the antagonist tooth has erupted and its almost certain the tooth located on the other side has erupted. Impacted tooth is partially erupted or cannot be erupted entirely because it is blocked by bone or soft tissue or both. The most commonly place where the impacted tooth can be found are mandibular and maxillary third molars, maxillary canines, mandibular premolars and supernumerary teeth.Methods: The odontectomy performed was the same as in other cases. Making a flap to get a field of view when extracted and carried out the division in the lower second molar teeth into several parts.Results: The results 6 months after the odontectomy, no abnormalities and healing in the bones were seen after the procedure.Conclusion: From this case report, it can be conclude that impacted tooth can also occur in other tooth, for example in mandibular second molars. Not only the third molars, canines, premolars or supernumerary teeth.